2018
DOI: 10.1002/ejp.1320
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain in adults born preterm: Evidence from two birth cohort studies

Abstract: Background Individuals born preterm are at risk of later developmental problems and long‐term morbidities. There is conflicting evidence regarding musculoskeletal pain in young adulthood. We investigated the prevalence of self‐reported musculoskeletal pain in young adults born across the range of preterm birth compared with a term‐born reference group. Methods From two Finnish birth cohorts, 184 individuals born early preterm (<34 weeks), 350 late preterm (34 to <37 weeks) and 641 at term completed a self‐repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Studies have linked migraine to musculoskeletal symptoms (41) and dysfunctions (42). However, there is no clear association between gestational age and musculoskeletal pain: One cohort study reported an association between preterm birth and chronic pain (43), but other larger studies found no association between preterm birth and chronic pain in adolescents (44) or widespread musculoskeletal pain in young adults (45). With this background, the lack of association between gestational age and migraine in our study may not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked migraine to musculoskeletal symptoms (41) and dysfunctions (42). However, there is no clear association between gestational age and musculoskeletal pain: One cohort study reported an association between preterm birth and chronic pain (43), but other larger studies found no association between preterm birth and chronic pain in adolescents (44) or widespread musculoskeletal pain in young adults (45). With this background, the lack of association between gestational age and migraine in our study may not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating associations between preterm birth, neonatal experience and the incidence of chronic pain in later life are hampered by differences in patient populations, definition of chronic pain, methodology and outcome [14,[18][19][20][21](Table 1). In addition, differentiating persistent biological effects related to neonatal exposures, and subsequent modulation by psychosocial and environmental factors, becomes more difficult at older ages [22].…”
Section: Pain Report and Experience In Young Adultsmentioning
confidence: 99%